What Is Wrong With The Financial Performance Of PT Waskita Karya Tbk? - Ramdani, Rahmat Fajar; Pratomo, Dimas (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2024)
This research aims to understand the financial performance condition of PT. Waskita Karya, Tbk based on observations over the past 5 years. The financial performance in this study utilizes 3 aspects of financial performance indicators: profitability, liquidity, and leverage. The observation period for this research is from 2018 to 2022, and the data used are secondary data obtained directly from the annual reports of PT. Waskita Karya, Tbk. The research employs Return On Asset (ROA) and Return on Equity (ROE) ratios as indicators of profitability, current ratio and operating cash flow ratio for liquidity measurement, and debt to asset (DTA) and debt to equity (DTE) ratios for leverage measurement. The analysis method used in this study is descriptive. The research results indicate that the financial performance of PT. Waskita Karya, Tbk over the past 5 years, based on the description of profitability, liquidity, and leverage indicators, is in an unfavorable condition.